2022
DOI: 10.36877/pmmb.a0000323
|View full text |Cite
|
Sign up to set email alerts
|

Anti-SARS-CoV-2 Biotherapeutics and Chemotherapeutics: An Insight into Product Specifications and Marketing Dynamics

Abstract: Chemotherapeutics and biotherapeutics agents have been explored as a potential treatment for COVID-19. This study was aimed to elucidate latest update related to biotherapeutics and chemotherapeutics against COVID-19 and its variants as well as the product specifications and marketing dynamics of its pharmacotherapies. There are several chemotherapeutics that have been studied for the treatment of COVID-19, including Paxlovid (Nirmatrelvir & Ritonavir) fixed dose combination, nirmatrelvir and ritonavir fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
(99 reference statements)
0
6
0
Order By: Relevance
“…Before vaccines for COVID-19 were available, Brunei was one of the many countries in the Asia Pacific Region that had participated in the WHO-led Solidarity trial, recognizing the critical importance of global collaborative efforts on the prevention and treatment of COVID-19 [76] . The trial was a global effort to compare the safety and effectiveness of biotherapeutics using different combinations of remdesivir, Iopinavir/ritonavir, interferon beta, chloroquine and hydroxychloroquine, as early as April 2020 [77,78] . A wide range of vaccine types were authorized by the Brunei Darussalam Medicines Control Authority (BDMCA) under Emergency Use Authorization to achieve herd immunity.…”
Section: Vaccination Programmentioning
confidence: 99%
“…Before vaccines for COVID-19 were available, Brunei was one of the many countries in the Asia Pacific Region that had participated in the WHO-led Solidarity trial, recognizing the critical importance of global collaborative efforts on the prevention and treatment of COVID-19 [76] . The trial was a global effort to compare the safety and effectiveness of biotherapeutics using different combinations of remdesivir, Iopinavir/ritonavir, interferon beta, chloroquine and hydroxychloroquine, as early as April 2020 [77,78] . A wide range of vaccine types were authorized by the Brunei Darussalam Medicines Control Authority (BDMCA) under Emergency Use Authorization to achieve herd immunity.…”
Section: Vaccination Programmentioning
confidence: 99%
“…There is a growing number of studies investigating the potential of exopolysaccharides as antiviral agents [264][265][266] . Table 7 presents a comprehensive summary of these studies, including information about the origin of bacterial EPS and the viral strains tested, in addition to the antiviral methods employed.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…For example, anakinra and baricitinib, previously employed for rheumatoid arthritis treatment, can be repurposed to treat COVID-19 infection since these drugs can reduce inflammation in host cells [34] . Several biotherapeutics and chemotherapeutics, including Paxlovid (Nirmatrelvir & Ritonavir) fixed-dose combination, chloroquine and hydroxychloroquine, Nirmatrelvir and Ritonavir fixeddose combination, Molnupiravir, Favipiravir, Remdesivir (Vekulary/Covifor) fixeddose combination, methylprednisole, Ivermectin and Infliximab (Remsima®) fixeddose have also been studied for their potential to be repurposed for the treatment of COVID-19 based on their anti-viral and anti-inflammation properties [35] . In battling long-term COVID-19 infection, a recent study showed that probiotics could be an adjunct therapy for COVID-19 treatment and its associated psychological symptoms.…”
Section: Bnt162b2mentioning
confidence: 99%